Respuestas

2013-08-09T01:53:22+02:00
1)     2y + x = -3                         x + 2y = -3
          x + y = -1                       -x  -  y  =   1        multiplicando por -1
                                                         y = -2    entonces  x = 1

2)       4x + 9y = 106                       -8x - 18y = -212     multiplicando por -2
          8x + 17y = 198                      8x +17y =  198
                                                               -y =   -14
                                                                 y = 14   entonces x = -5

3)    -6x +  y = -1                     -6x + y =   -1
        2x - 3y = -5                      6x - 9y = -15       multiplicando por 3
                                                      -8y = -16
                                                          y = 2    entonces    x = 1/2